2017
DOI: 10.1177/0306624x17692060
|View full text |Cite
|
Sign up to set email alerts
|

Body Disposal: Spatial and Temporal Characteristics in Korean Homicide

Abstract: This study explores the body disposal patterns in a sample of 54 Korean homicides that occurred between 2006 and 2012. Based on information collected by the police during their investigation, factors that could influence body disposal patterns were examined, such as homicide classification, intention, whether an accomplice was present, and offender mental disorder. Bivariate analyses showed that the majority of the victims who were disposed of were acquaintances of the offenders. Moreover, several offenders we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…The differences in routine activities of the offenders and the victim could also account for the differences observed in the crime locations. Thus, Canadian SHOs disposed of the body at an outdoor location almost twice as often as Korean SHOs and NSHOs, which is in accordance with Sea and Beauregard (2018, 2016) and Salfati and Park (2007).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The differences in routine activities of the offenders and the victim could also account for the differences observed in the crime locations. Thus, Canadian SHOs disposed of the body at an outdoor location almost twice as often as Korean SHOs and NSHOs, which is in accordance with Sea and Beauregard (2018, 2016) and Salfati and Park (2007).…”
Section: Discussionsupporting
confidence: 58%
“…In another study looking at body disposal of Korean homicidal offenders including sexual homicides, Sea and Beauregard (2018) found that most bodies were disposed within a few hours after the murder, usually occurring during the middle of the night. This temporal pattern is different from previous studies originating from the United States and Canada (i.e., Hanfland, Keppel, & Weis, 1997; Nethery, 2004; Rossmo, 2008), where bodies can be disposed of during daytime or hours after the homicide.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that close to half of stranger homicides involved an accomplice, and the majority of the offenders had access to a vehicle, which indicates the significance of pre-crime factors. Further, results showed that most bodies were dumped in wooded or agriculture areas, suggesting that offenders made rational choices in selecting deserted areas to dispose of the victim's body (Sea & Beauregard, 2018). In terms of geographic distance, the authors found that the majority of offenders committed the crime close to where they first encountered their victim (0.3 km) but were willing to travel up to 30 km to dump the victim's body.…”
Section: Post-crime Phase: Body Disposal Patternsmentioning
confidence: 99%
“…A recent study conducted by Sea and Beauregard (2018) investigated 54 Korean homicide cases and found several factors which influenced body disposal patterns. The authors found that close to half of stranger homicides involved an accomplice, and the majority of the offenders had access to a vehicle, which indicates the significance of pre-crime factors.…”
Section: Post-crime Phase: Body Disposal Patternsmentioning
confidence: 99%
See 1 more Smart Citation